Effectiveness of Structured Teaching Programme on Knowledge Regarding Risk Factors and Prevention of Osteoporosis Among Premenopausal Women - J. Dhanalakshmi (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Bone is a living, dynamic tissue that undergoes constant remodeling throughout life. This is necessary to allow the skeleton to increase in size during growth, respond to the physical stresses placed on it and repair structural damage due to structural fatigue or fracture. This process requires range of proteins and minerals, which are absorbed from the blood stream.Osteoporosis is often known as the silent thief because bone loss occurs without symptoms; one in four women over the age of 50 has osteoporosis. One in eight men over 50 year also has the disease. However, the disease can strike at any age. More women die each year as a result of osteoporotic fractures than from breast and ovarian cancer. This quasi experimental design was undertaken to assess the effectiveness of structured teaching programme on knowledge regarding risk factors and prevention of osteoporosis among premenopausal women. 50 premenopausal women were selected by convenience sampling method at ammapalayam village. Conceptual frame work was modified Rosan's stock health belief model was adopted for the study. The data was collected by using structured interview schedule. It is inferred that majority of the pre-menopausal women who participated in the study was aged between 30-45 years, coolie, higher secondary, married and income more than 3000-5000. Pre -test shows 43(86%) had inadequate knowledge, 7(14%) had moderate knowledge and none of them had adequate knowledge. The paired‘t’ test was used to evaluate the effectiveness of structured teaching programme by comparing pre-test and post-test knowledge score. It was found that pre-test mean knowledge score was 6.72(SD=2.7) and post-test mean knowledge score was 20.64(SD=2.05) and paired ‘t’ value was 28.819*.The observed value of paired t-test is not less than the table value at (p<0.05).So the research hypothesis was accepted. It is evident that the post-test knowledge score on risk factors and prevention of osteoporosis is significantly higher than the pre-test score. There was a significant association between the pre-test knowledge score on risk factors and prevention of osteoporosis with income among premenopausal women.